Decreasing of Mangan (II) in The Water Using Membrane of Moringa Seed Powder-TiO2 with Variation of Mass TiO2 - Ana Hidayati Mukaromah; Fandhi Adi Wardoyo; Ayu Rahmawati Sulistyaningtyas; Haikal Naufal Ghazi (Jurnal Riset Kimia, 2023)
Mn (II) is a metal ion commonly used in steel alloys, pigment industries, welding, fertilizers, pesticides, ceramics, and electronics. According to the Regulation of the Minister of Health No. 32 of 2017, the permissible content of Manganese in dug well water is 0.5 mg/L. The purpose of this study was to determine the concentration of Mn (II) ions in water before and after passing through a Moringa Seeds Powder (MSP)-TiO2 membrane 20:1; 20:3; 20:5; 20:7; 20:9 and measure the percentage decrease in the concentration of Mn (II) ions in water after through the MSP-TiO2 membrane. The object of this research is a 55 ppm Mn (II) ion artificial sample at a flow rate of 0.56 mL/minute for 90 minutes with 90-watt radiation UV. The concentration of Mn (II) ion was measured by visible spectrophotometric method, the morphology of MSP, TiO2, and MSP-TiO2 membranes was characterized by SEM-EDX, and its diffraction spectra by X-Ray diffraction. The results obtained that the initial Mn(II) was 55.06 ± 0.031 ppm, the concentration of Mn (II) ions with the MSP-TiO2 membrane of mass MSP-TiO2 were 20:1; 20:3; 20:5; 20:7; 20:9 respectively 36.47±0.00; 44.16±1.15; 44.31±1.04; 44.94±0.94; 42.27±2.61 ppm. The percentage of decrease concentration of Mn (II) ion are 34.19±0.44%; 21.37±0.43%; 20.94±0.85%; 19.24±0.86%; and 19.66±0.86%. The highest percentage decrease in Mn (II) ion concentration was 34.15±0.44% in the variation of mass MSP-TiO2 20:1. This study concludes that the MSP-TiO2 membrane has the potential to reduce the concentration of Mn (II) ions in water.